Effect of reperfusion time on right ventricular remodeling in inferior ST-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention - Probokusumo, Jagaddhito; Mumpuni, Hasanah; Sanggula, Pratiwi Noor Purnama Putri Sanggula; Bagaswoto, Hendry Purnasidha (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Right ventricle (RV) remodeling and dysfunction are frequent in inferior ST-elevation myocardial infarction (STEMI) patients and possibly implicated to poor outcomes. Objective: The purpose of this study is to investigate the influence of reperfusion time on RV remodeling in patients with inferior STEMI who had primary percutaneous coronary intervention (PPCI). Methods: The subjects were patients with inferior STEMI who had undergone PPCI and met the inclusion and exclusion criteria. From September 2021 to April 2022, samples were taken in the order in which they arrived at the Dr. Sardjito Hospital in Yogyakarta, Indonesia. To investigate the occurrence of RV remodeling, 2D-transthoracic echocardiography was performed before PPCI as baseline and 3-months after PPCI. Confounding factors were investigated using bivariate and multivariate analysis. Results: The RV remodeling was observed in 12 (28.6%) of 42 inferior STEMI patients undergoing PPCI. The RV remodeling group had a longer median reperfusion time (798.5 vs 710 minutes, p=0.568). The baseline RV end-systolic area (RVESA) and RV end-diastolic area (RVEDA) had significant correlations with the occurrence of RV remodeling (p=0.046; p=0.008, respectively). The tricuspid annular plane systolic excursion (TAPSE) rose considerably in both groups during the 3-month follow up. There were significant variations in RVEDA and RV basal diameter in the RV remodeling group, but there was a substantial rise in fractional area change (FAC) and RVESA in the non-RV remodeling group. Conclusion: In patients with inferior STEMI undergoing PPCI, reperfusion time showed no significant effect on RV remodeling.